THE EFFECTIVENESS OF BLIND CODES AND SECURITY FEATURES FOR THE BLIND AND THE PREVENTION OF FRAUD ON THE INDONESIAN RUPIAH - Tri Hartono; Fitra Roman Cahaya (Asia Pacific Fraud Journal, 2017)
ABSTRACTBlind codes and security features are very important for the people with visual impairment to recognize banknotes denomination. One of the problems commonly experienced by the blind Indonesian is how to detect the nominal value and the authenticity of the banknotes. It is suspected that blind codes and security features existing on the Indonesian banknotes are less effective to help the blind detect the banknotes. That is why it is very interesting to analyze the level of effectiveness of blind codes and security features on the Indonesian banknotes, especially for the people with visual impairment. The experimental result shows that security features and blind codes are less effective for the people with visual impairment. It is assumed that the ineffectiveness will increase when the banknotes are in an outdated or crumpled condition. The authors gave treatment to respondents by giving Indonesian banknotes, which had been provided with Braille letter. Based on the experiment using Braille letter, 96% of respondents were able to detect and enumerate the nominal value of the banknotes appropriately.This ineffectiveness is feared to have an impact on the increasing circulation of counterfeit money in the community. It would be even more frightening when people become a medium of spreading counterfeit money in the community just because of the ineffectiveness of the design of banknotes and the lack of education of the blind Indonesian.